Bridging the Gap for Children With Compound Health Challenges: An Intervention Protocol - Elgen, Irene; Heggestad, Torhild; Tronstad, Rune; Greve, Gottfried (Frontiers in Pediatrics, 2021)
Background: During the last decades, there is a major shift in the panorama of diseases in children and adolescents. More children are referred to the specialized health care services due to less specific symptoms and more complex health challenges. These children are particularly difficult to care for in a “single-disease” oriented system. Our objective was to develop an alternative and more holistic approach better tailored to the complex needs of these children. Method: The target patient population is children between 6 and 13 years with three or more referrals including both the pediatric department and the mental health services. Furthermore, to be included in the project, the child's actual complaints needed to be clinically considered as an unclear or compound condition in need of an alternative approach. This paper describes the process of developing an intervention where a complementary professional team meets the patient and his/her family altogether for 2.5 h. The consultation focus on clarifying the complex symptomatology and on problem solving. The bio-psycho-social model is applied, emphasizing the patient's story as told on the whiteboard. In the dynamic processes of development, piloting, evaluating, and adjusting the components, feed-back from the patients, their families, professional team members, and external team coaches is important. The professional teams include pediatricians, psychologists and physiotherapists. Achieving the transformation from a logistic oriented team where members act separately toward a real complementary team, seems to be a success factor. Discussion: Composing multi-disciplinary and complementary teams was an essential part of the re-designed intervention. Team interaction transforming the professionals from working as a logistic team to act as a complementary team, was one of the important requirements in the process. When re-designing the specialist health service, it is mandatory to anchor all changes among employees as well as the hospital leadership. In addition, it is important to include patient experiences in the process of improvement. Evaluation of long-term outcomes is needed to investigate possible benefits from the new intervention. Trial Registration: Transitioning Young Patients' Health Care Trajectories, NCT04652154. Registered December 3rd, 2020–Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT04652154?term=NCT04652154&draw=2&rank=1.